2020
DOI: 10.1515/humor-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

The traditional sexual script and humor in courtship

Abstract: To account for sex differences in the production, receptivity, and preference for humor in potential mates during courtship, past research has often adopted an evolutionary approach. The present manuscript will attempt to integrate evolutionary explanations with proximal social and cultural influences using the traditional sexual script and ambivalent sexism theory. The results of both Study 1 (N=227) and Study 2 (N=424) suggest that trait masculinity is positively associated with humor production in courtship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…This research adds to prior work on the use of aggressive humor by providing evidence that differentiates the Contests Hypothesis of the use of aggressive humor from the Mate-Choice Hypothesis. Prior research on aggressive humor under the framework of evolutionary psychology ( Bressler and Balshine, 2006 ; Bressler et al, 2006 ; Greengross and Miller, 2008 , 2011 ; Wilbur and Campbell, 2011 ; Cowan and Little, 2013 ; DiDonato et al, 2013 ; Zeigler-Hill et al, 2013 ; Hone et al, 2015 ; Ross and Hall, 2020 ) almost exclusively focused on the effect of using aggressive humor on users’ perceived desirability as a long- or short-term mate and mating success. However, those findings do not support either the Contests Hypothesis or the Mate-Choice Hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research adds to prior work on the use of aggressive humor by providing evidence that differentiates the Contests Hypothesis of the use of aggressive humor from the Mate-Choice Hypothesis. Prior research on aggressive humor under the framework of evolutionary psychology ( Bressler and Balshine, 2006 ; Bressler et al, 2006 ; Greengross and Miller, 2008 , 2011 ; Wilbur and Campbell, 2011 ; Cowan and Little, 2013 ; DiDonato et al, 2013 ; Zeigler-Hill et al, 2013 ; Hone et al, 2015 ; Ross and Hall, 2020 ) almost exclusively focused on the effect of using aggressive humor on users’ perceived desirability as a long- or short-term mate and mating success. However, those findings do not support either the Contests Hypothesis or the Mate-Choice Hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by mating with a funnier person, one is more likely to mate with a higher quality partner and produce higher quality offspring. In this process, men would generally be more motivated than women to produce humor ( Greengross et al, 2020 ; Ross and Hall, 2020 ) because men typically face more intense intrasexual competition and thus more motivated to invest in courtship display, including humor production. In response, women should value men’s ability to produce humor ( Bressler and Balshine, 2006 ; DiDonato et al, 2013 ; Hone et al, 2015 ; Tornquist and Chiappe, 2015 ), perceive romantic interest in men producing humor ( Tornquist and Chiappe, 2020 ), and find men with relatively high humor capability to be attractive ( Bressler and Balshine, 2006 ; Driebe et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The friendliness of a humor display could implicate men as exhibiting the requisite kindness for long-term pairbonds, which would correspond with the desirability of extraversion in romantic relationships (DiDonato et al, 2013;Figueredo et al, 2006). Conversely, the dynamics of humor in mating domains could have masculine undertones that could connote a dominance that limits the desirability of extraversion to short-term pairbonds (Brown & Sacco, 2017;Ross & Hall, 2020). Masculinity is broadly an ambivalent cue in mating connoting both heritable fitness and extraversion while similarly connoting the potential for hostility and disinterest in long-term relationships (Brown et al, 2022c;Frederick & Haselton, 2007;Geniole & McCormick, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The competence connoted through humor could implicate funny men as capable of satisfying LTM goals, as shown by the previous study. Conversely, the general masculinity of humor as a mating display from men could implicate them as particularly dominant (Ross & Hall, 2020), which would limit their desirability to STM (Frederick & Haselton, 2007). Additionally, previous research has suggested that humor displays in mating domains could implicate men as disinterested in monogamous pairbonding and untrustworthy in LTM (Bressler & Balshine, 2006;Medlin et al, 2018).…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation